Digital Pathways to Safer Motherhood: A Narrative Review of mHealth’s Role in Achieving Sustainable Development Goal 3 - Mondal, Ananya; Chanu, Takhellambam Kiranmala; Patel, Nita; Khatun, Jeba; Nitrina Devi, Wangkheirakpam; Kundu, Komol (Journal of Neonatal Surgery, 2025)
Background: Maternal and neonatal mortality remain pressing global health issues, particularly in low-resource settings. Barriers such as limited access to skilled care, delayed referrals, and insufficient health education contribute significantly to adverse outcomes. As part of the effort to achieve Sustainable Development Goal 3–ensuring healthy lives and well-being for all— mHealth is emerging as a key tool in transforming maternal care through digital innovation. Objectives: This review explores the contribution of mHealth in improving maternal and neonatal outcomes, focusing on its effectiveness in reducing mortality and supporting global advancement of SDG3. Methods: A comprehensive literature search was conducted using PubMed, Scopus, Web of Science, and Google Scholar for publications between 2010 and 2024. Peer-reviewed articles, pilot programs, and digital health reports were reviewed. Selection criteria focused on community-based mHealth tools used for maternal and newborn care. Results: mHealth interventions demonstrated improvements in maternal service utilization, care-seeking behaviour, antenatal visit attendance, institutional deliveries, and emergency care access. Tools like MomConnect, mMitra, and MOTECH enhanced maternal awareness and care continuity. Apps such as CommCare and the Safe Delivery App improved health worker competencies. Programs including RapidSMS, TulaSalud, Ananya mHealth, Text4Baby and WelTel and GiftedMom contributed to reduced neonatal mortality through improved tracking, referrals, and health education. Conclusion: mHealth technologies are reshaping maternal and neonatal healthcare in low-resource settings by bridging communication gaps and improving access to services. Continued innovation, investment and integration into national health systems are essential for scaling their impact to achieve SDG 3.